Characteristics of Brain White Matter Microstructure in HIV Male Patients With Primary Syphilis Co-Infection - Qi, Yu; Li, Rui-Li; Wang, Yuan-Yuan; Wang, Wei; Liu, Xu-Ze; Liu, Jing; Li, Xing; Zhang, Xiao-Dong; Yu, Wen; Liu, Jiao-Jiao; Guo, Yi-Fan; Rao, Bo; et al. (Frontiers in Neurology, 2022)
Purpose: To investigate the effect of syphilis infection on the microstructure of white matter (WM) in HIV-infected male patients using diffusion tensor imaging (DTI). Methods: Twenty-seven HIV-infected male patients with current syphilis or a history of syphilis (HIV +/syphilis +), twenty-nine HIV-infected male patients without syphilis co-infection (HIV +/syphilis–), and twenty-nine healthy controls (HC) were enrolled. All participants received DTI, and all patients received comprehensive neuropsychological assessment. Tract-based spatial statistics (TBSS) was adopted to analyze the DTI measures: fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD). Correlation analysis was conducted to investigate the relationships between DTI measures and cognitive performance. Results: There were no significant differences in DTI measures between HIV+/syphilis– and HC. Compared with HC, lower FA was found in body of corpus callosum (BCC), splenium of corpus callosum (SCC), genu of corpus callosum (GCC), the bilateral anterior corona radiata (ACR), superior corona radiata (SCR), posterior corona radiata (PCR), and posterior thalamic radiation (PTR) in HIV+/syphilis+ (p < 0.05). Higher RD was found in BCC and SCC (p < 0.05). Compared with HIV+/syphilis–, lower scores were found in complex motor skills (CMS) in HIV+/syphilis+, lower FA was found in BCC, SCC, GCC, the bilateral ACR, SCR, PCR, PTR, cingulate gyrus (CGC), the right inferior fronto-occipital fasciculus (IFO), the retrolenticular part of internal capsule (RLIC), sagittal stratum (SS), external capsule (EC) in HIV+/syphilis+ (p < 0.01). Correlation analysis uncorrected for multiple comparisons showed there was a positive correlation between FA in GCC and CMS, FA in BCC, and CMS in HIV+/syphilis+. Conclusions: Syphilis co-infection can have an additive or synergistic effect on the brain WM in HIV-infected subjects. HIV-infected patients without syphilis should be actively treated to avoid syphilis infection.